Voltage stability of a photovoltaic DC microgrid using fuzzy logic controller - Manohar, Kalangiri; Padma, Kottala (International Journal of Applied Power Engineering (IJAPE), 2024)
This article employs a fuzzy logic controller (FLC) to investigate voltage stability in a PV-based DC microgrid. Several photovoltaic (PV) modules, a DC-DC converter, and loads make up the microgrid. Due to the widespread use of intermittent PV power, voltage stability is a crucial problem for DC microgrids and is difficult to accomplish. This study proposes an FLC-based voltage control technique that leverages input factors including PV output power, DC-DC converter duty cycle, and load current to identify the best course of action for preserving the system's voltage stability. The FLC's performance is assessed by simulation, and it is meant to be resilient to parameter fluctuations and uncertainties. The simulation results demonstrate that the suggested FLC-based control strategy successfully maintains the microgrid's voltage stability under a variety of operational circumstances, including changing solar irradiance and load variations. Moreover, the FLC performs better than other control methods.